2016
DOI: 10.1007/s13762-016-0954-y
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chromate from wastewater using amine-based-surfactant-modified clinoptilolite

Abstract: This study presents the results of chromate adsorption upon organically modified clinoptilolite obtained by the treatment of Bigadic clinoptilolite with surfactants in primary amine structure, namely 1-dodecylamine, 1-hexadecylamine and oleylamine. Natural and organo-clinoptilolites were characterized by X-ray diffraction, thermal gravimetry and Fourier transform infrared spectrometry which proved the integration of amine groups followed by the order oleylamineOrgano-clinoptilolites were tested for their effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Organically modified clinoptilolites are commonly produced by treating clinoptilolite with organic agents such as cationic surfactants [ 34 , 35 , 36 , 63 , 64 ], polymers [ 65 , 66 ], or amines [ 38 , 40 , 48 , 67 ]. The organic modification intensely changes the surface properties, allowing clinoptilolite to sorb anions or nonpolar molecules, for which the unmodified surface has a little affinity.…”
Section: Modification Of Clinoptilolitementioning
confidence: 99%
See 2 more Smart Citations
“…Organically modified clinoptilolites are commonly produced by treating clinoptilolite with organic agents such as cationic surfactants [ 34 , 35 , 36 , 63 , 64 ], polymers [ 65 , 66 ], or amines [ 38 , 40 , 48 , 67 ]. The organic modification intensely changes the surface properties, allowing clinoptilolite to sorb anions or nonpolar molecules, for which the unmodified surface has a little affinity.…”
Section: Modification Of Clinoptilolitementioning
confidence: 99%
“…Wingenfelder et al [ 40 ] treated natural clinoptilolite with cysteamine and propyl amine with the aim to remove Cd and Pb and found that amine-modified clinoptilolite could not be effectively used for this purpose. In the research performed by Guzel et al [ 48 ], the interaction of natural clinoptilolite with primary amines including 1-dodecylamine, 1-hexadecylamine, and oleylamine was investigated. Results proved that the integration of amine groups was directly proportionate to the length of the hydrocarbon tail.…”
Section: Modification Of Clinoptilolitementioning
confidence: 99%
See 1 more Smart Citation
“…Cr can exist in all oxidation states from 0 to VI, the most common oxidation states in water being Cr III and Cr VI . In an aqueous environment, the toxicity of Cr VI has been shown to be greater than that of Cr III (Guzel et al, 2016). Transition metal complexes of the cyclam (1,4,8,11-tetraazacyclotetradecane, C 10 H 24 N 4 ) ligand have been the subject of numerous investigations because of their particular conformational stereochemistry (Poon & Pun, 1980;Choi, 2009;Subhan et al, 2011).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Therefore, knowledge of the conformation and hydrogen-bonding interactions in Cr III -Cr VI complex systems containing the cyclam ligand has become important in the development of new anti-HIV drugs (De Clercq, 2010). The use of such complexes for the more effective removal of toxic metals is also important (Guzel et al, 2016). As part of a study of the conformation and structure of (cyclam)chromium(III) complexes with auxiliary ligand(s) and various anions, we ISSN 2056-9890 report here the structural characterization of the new complex salt, [Cr(C 2 O 4 )(C 10 H 24 N 4 )] 2 [Cr 2 O 7 ]Á8H 2 O, (I).…”
Section: Chemical Contextmentioning
confidence: 99%